Implementasi Work-Life Balance dalam Meningkatkan Kinerja Karyawan Milenial - Delyana Rahmawany Pulungan; Susantriana Dewi; Niken Widyastuti; Muthmainnah; Nicholas Renaldo (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The purpose of this study is to determine the implementation of work life balance in improving the performance of millennial employees. This research approach collects data through literature studies, which involve reading literature from various sources including books, journals and reports using qualitative and deductive approaches. The findings in this study are that work life balance is a key factor in improving the performance of millennial employees. By providing flexibility in time and work location, creating a healthy and positive work culture, implementing health and well-being programs, career development and training, and using technology for work efficiency. So with this, the company can improve employee performance. Companies that successfully implement work life balance well will not only benefit in the form of improved employee performance, but will also have a reputation as an attractive workplace for the millennial generation and the next generation.